From ELISA to Immunosorbent Tandem Mass Spectrometry Proteoform Analysis: The Example of CXCL8/Interleukin-8 - Metzemaekers, Mieke; Abouelasrar Salama, Sara; Vandooren, Jennifer; Mortier, Anneleen; Janssens, Rik; Vandendriessche, Sofie; Ganseman, Eva; Martens, Erik; Gouwy, Mieke; Neerinckx, Barbara; Verschueren, Patrick; De Somer, Lien; et al. (Frontiers in Immunology, 2021)
With ELISAs one detects the ensemble of immunoreactive molecules in biological samples. For biomolecules undergoing proteolysis for activation, potentiation or inhibition, other techniques are necessary to study biology. Here we develop methodology that combines immunosorbent sample preparation and nano-scale liquid chromatography – tandem mass spectrometry (nano-LC-MS/MS) for proteoform analysis (ISTAMPA) and apply this for the aglycosyl chemokine CXCL8. CXCL8, the most powerful human chemokine with neutrophil chemotactic and –activating properties, occurs in different NH2-terminal proteoforms due to its susceptibility to site-specific proteolytic modification. Specific proteoforms display up to 30-fold enhanced activity. The immunosorbent ion trap top-down mass spectrometry-based approach for proteoform analysis allows simultaneous detection and quantification of full-length CXCL8(1-77), elongated CXCL8(-2-77) and all naturally occurring truncated CXCL8 forms in biological samples. For the first time we demonstrate site-specific proteolytic activation of CXCL8 in synovial fluids from patients with chronic joint inflammation and address the importance of sample collection and processing.